(untitled) (Asian Journal of Current Engineering and Maths, 2013)
The purpose of this paper is to introduce and study the concepts of intuitionistic fuzzy Ï€-generalized semi-pre closed sets and intuitionistic fuzzy Ï€-generalized semi-pre open sets in Intuitionistic fuzzy topological space. We investigate some of their properties